Long noncoding RNA GDIL acts as a scaffold for CHAC1 and XRN2 to promote platinum resistance of colorectal cancer through inhibition of glutathione degradation - Xuan Deng; Lu Chang; Lingyu Tang; Haoqin Jiang; Xiao Xu; Xinju Zhang; Jian Chen; Liu Dong; Qianqian Xu; Ruoshui Cao; Jianbin Xiang; Ming Guan (Cell Death and Disease)
Abstract Acquired resistance poses a significant obstacle to the effectiveness of platinum-based treatment for cancers. As the most abundant antioxidant, glutathione (GSH) enables cancer cell survival and chemoresistance, by scavenging excessive reactive oxygen species (ROS) induced by platinum. Therapeutic strategy targeting GSH synthesis has been developed, however, failed to produce desirable effects in preventing cancer progression. Thus, uncovering mechanisms of rewired GSH metabolism may aid in the development of additional therapeutic strategies to overcome or delay resistance. Here, we identify upregulation of long noncoding RNA (lncRNA) GDIL (GSH Degradation Inhibiting LncRNA) in platinum resistant colorectal cancer (CRC) and ovarian cancer cells compared with parental ones. High expression of GDIL in resistant CRC is associated with poor survival and hyposensitivity to chemotherapy. We demonstrate that GDIL boosted GSH levels and enhances clearance of ROS induced by platinum. Metabolomic and metabolic flux analysis further reveals that GDIL promotes GSH accumulation by inhibiting GSH degradation. This is attributed by downregulation of CHAC1, an enzyme that specifically degrades intracellular GSH. Mechanistically, GDIL binds and re-localizes the nuclear protein XRN2 to the cytoplasm, where GDIL further serve as a scaffold for XRN2 to identify and degrade CHAC1 mRNA. Suppression of GDIL with selective antisense oligonucleotide, restored drug sensitivity in platinum resistant cell lines and delayed drug resistance in cell line- and patient-derived xenografts. Thus, lncRNA GDIL is a novel target to promote GSH degradation and augment platinum therapy.